PEMBELAJARAN LITERASI SISWA KELAS X SMA PGRI I DENPASAR: MODEL PEMBELAJARAN LINGUISTIK FUNGSIONAL SISTEMIK - Januario Mario Ohoiwutun; Muhammad Adha Manuhutu; Intan Amelia; I Ketut Suardana (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
This paper aims to describe the literacy learning process for tenth-grade students at PGRI I Senior High School, Denpasar. This learning process was conducted by three English Language Study Program students at Bali Dwipa University in the 2025/2026 academic year as part of the study program's Field Work Practice program. This program aims to apply the theories learned during their studies at the English Language Study Program at Bali Dwipa University. The internship lasted two months, from September 15 to November 15, 2025. The learning model used in this course is Systemic Functional Linguistics, which emphasizes social context, cultural context, and ideology. This learning model was chosen because it ties together the social context that occurs in society. This learning is expected to contribute to understanding how to comprehend texts as a whole and how to rephrase them in one's own language. The output of this learning process is the ability to identify moral messages contained in texts and to provide comprehensive education to the general public. This paper provides benefits to the field of linguistics, such as: Language Learning, Philosophy of Language, Semantics, Sociolinguistics, Semiotics, Pragmatics, Psycholinguistics, and Discourse.